2021
DOI: 10.1101/2021.04.13.439638
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

pUL21 is a viral phosphatase adaptor that promotes herpes simplex virus replication and spread

Abstract: The herpes simplex virus (HSV)-1 protein pUL21 is essential for efficient virus replication and dissemination. While pUL21 has been shown to promote multiple steps of virus assembly and spread, the molecular basis of its function remained unclear. Here we identify that pUL21 is a virus-encoded adaptor of protein phosphatase 1 (PP1). pUL21 directs the dephosphorylation of cellular and virus proteins, including components of the viral nuclear egress complex, and we define a conserved non-canonical linear motif i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…An alternative explanation for the hyperphosphorylation of pUs3, pUL31 and pUL34 in ΔUL21 infected cells is that pUL21 may promote their dephosphorylation (Figure 9B). This idea is strongly supported by a recent unpublished study from Graham and co-workers that demonstrated HSV-1 pUL21 is an adaptor protein for protein phosphatase 1 (PP1) and furthermore that pUL21 has a penchant for delivery of PP1 to pUs3 substrates to mediate their dephosphorlyation [36]. The fact that pUL21 and pUs3 are only found in members of the Alphaherpesvirinae raises the intriguing possibility that pUL21 exists, in part, to specifically counter the activities of pUs3.…”
Section: Discussionmentioning
confidence: 91%
“…An alternative explanation for the hyperphosphorylation of pUs3, pUL31 and pUL34 in ΔUL21 infected cells is that pUL21 may promote their dephosphorylation (Figure 9B). This idea is strongly supported by a recent unpublished study from Graham and co-workers that demonstrated HSV-1 pUL21 is an adaptor protein for protein phosphatase 1 (PP1) and furthermore that pUL21 has a penchant for delivery of PP1 to pUs3 substrates to mediate their dephosphorlyation [36]. The fact that pUL21 and pUs3 are only found in members of the Alphaherpesvirinae raises the intriguing possibility that pUL21 exists, in part, to specifically counter the activities of pUs3.…”
Section: Discussionmentioning
confidence: 91%